Expression of Smooth Muscle Calponin in Synovial Sarcoma. (1999) - Ono, Hidefumi; Yoshikawa, Hideki; Ueda, Takafumi; Yamamura, Hisako; Kudawara, Ikuo; Manou, Masayuki; Ishiguro, Shingo; Funai, Hiroko; Koyanagi, Yumiko; Araki, Nobuhito; Hashimoto, Nobuyuki; Sonobe, Hiroshi; et al.
Abstract : Purpose. Histogenesis of synovial sarcoma remains controversial and reliable molecular markers for diagnosis are necessary. Expression of basic calponin, a smooth muscle differentiation-specific actin-binding protein, was studied in synovial sarcoma. Subjects and Methods. The basic calponin gene and the gene product were analyzed by reverse transcription PCR analysis (RT-PCR) and immunohistochemistry in 14 synovial sarcomas and a human synovial sarcoma cell line (HS-SY-II). Results and Discussion. Immunoreactivity for basic calponin was detected in the cytoplasm of 6 synovial sarcomas (43% positive). In the basic calponin-positive tumors and the HS-SY-II cells, expression for smooth muscle-specific genes, including basic calponin and SM22α, was detected by RT-PCR, suggesting a lineage relationship between synovial sarcoma cells and smooth muscle-like mesenchymal cells. Conclusions. A subset of synovial sarcomas expressing the basic calponin gene and the gene product were identified. The basic calponin may have potential utility as a novel molecular marker identifying certain synovial sarcomas.